2008
DOI: 10.1108/17538330810889998
|View full text |Cite
|
Sign up to set email alerts
|

The role of stakeholders in town centre management: guidelines for identification and analysis

Abstract: Purpose -The purpose of this paper is to provide insights into the identification of stakeholders involved in town centre management (TCM) projects and the main areas of intervention according to their interests and needs. Design/methodology/approach -The proposed framework is tested in the town of Benevento, Italy. On the basis of stakeholder theory, key stakeholders were interviewed according to the different kinds of linkages they had with the TCM organisation. Findings -Results from the paper support a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 15 publications
0
56
1
2
Order By: Relevance
“…de Nisco, Riviezzo, and Napolitano 2008;Forsberg, Medway, and Warnaby 1999;Sandahl and Lindh 1995). de Nisco, Riviezzo, and Napolitano (2008) conclude that previous research views property owners as having a minor stakeholder role and that they are not as cooperative as other stakeholders. In contradiction to this, it has been found that retail siting (Forsberg 1998) and property constructions (Dawson 2001), as well as managing properties, are often closely related to retail's core business, which then connects the property owner to the retailer.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…de Nisco, Riviezzo, and Napolitano 2008;Forsberg, Medway, and Warnaby 1999;Sandahl and Lindh 1995). de Nisco, Riviezzo, and Napolitano (2008) conclude that previous research views property owners as having a minor stakeholder role and that they are not as cooperative as other stakeholders. In contradiction to this, it has been found that retail siting (Forsberg 1998) and property constructions (Dawson 2001), as well as managing properties, are often closely related to retail's core business, which then connects the property owner to the retailer.…”
Section: Introductionmentioning
confidence: 93%
“…Riviezzo, de Nisco, and Napolitano 2009;Otsuka and Reeve 2007;Whyatt 2004). As a result, concerns have been raised about the vitality and viability of a town centre (de Nisco, Riviezzo, and Napolitano 2008) leading to the need for strategic and proactive cooperation from all stakeholders (Riviezzo, de Nisco, and Napolitano 2009;Phillips and Swaffin-Smith 2004;Forsberg 1998). Consequently, stakeholder management has become important in the context of managing a town centre.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations